Descripción de las características sociodemográficas de los adultos mayores residentes en un centro gerontológico del cantón Ibarra - Gualpa Morán, Johselyn Carolina (2025)
The sociodemographic characteristics of the older adult are aspects that allow a detailed analysis of the conditions of the older adult, therefore the objective of this research is to describe the sociodemographic characteristics of the older adult population, in the León Rúales Gerontological Center of the Ibarra Canton in the period October 2024 - February 2025. The research uses a descriptive methodology, which allows detailing the current sociodemographic characteristics of the elderly, based on the collection of valuable information that allows them to be shown in their current context. The approach is mixed, not experimental\; The research technique used was documentary review and analysis. Regarding the research instrument, the digital content matrix was used. This tool was designed to organize and structure the information extracted from the clinical records of older adults residing at the León Rúales Gerontological Center of the Ibarra Canton. The presentation of results occurs through the tabulation of data obtained from the base of the investigated Center, which gives rise to precise information in order to serve as a basis for future research, and which, if applicable, allows creating action plans to improve the quality of life of the elderly.